Nitrogen fluorescence in air for observing extensive air showers - Keilhauer, B. (2012)
12 pages, 17 figures, 2 tables, International Symposium on Future Directions in UHECR Physics, 13-16 February 2012, CERN, Geneva (Switzerland); the updated version corrects for a typo in Eq. (1)